Analysis of Student Statistical literacy Using Test Questions integrated with Indonesian Education Issues as a form of Contextual approach - Habibie, Zulqoidi R; Kartono, Kartono; Kartono, Wardono; Kharisudin, Iqbal (Polyhedron International Journal in Mathematics Education, 2023)
This study aims to analyze the ability of SL using statistical literacy ability test questions integrated with Indonesian education issues through a quantitative descriptive research approach to 116 students of the Elementary School Teacher Education Study Program at Muhammadiyah University Muara Bungo. The results showed that students were still low in Statistical Literacy skills. These results can be seen from 75% of students who scored below 60 and 25% of students who scored above 60 on the Statistical Literacy ability test. Then, it can be seen from the average ability of students to solve SL test questions based on Indicators, namely 71.33% in indicator 1, 53.16% in indicator 2, and 57.18% in indicator 3. At the same time, the average student who is able to solve SL questions is 28.67% in indicator 1, 46.84% in indicator 2, and 42.82% in indicator 3. Based on in-depth interviews, researchers see the main factor in the low SL ability of students being that they have not mastered descriptive statistics. The main factor that helps students solve SL questions is the Indonesian Education Issue approach. Researcher suggest that further research needs to be done that can improve students' SL skills through the application of learning models, the development of learning models, or the application of learning strategies to solve SL problems.